Al-Wasaţiyah al-Intiqâiyah al-Taqlîdiyah: Dirâsat Haula Harakâti wa Afkâri Kiâi Hâjî Hâsyim Asy’arî fî Fiqh al-Siyâsah al-Ijtimâ’iyah bi Indûnîsiâ - Mohammad Hasan (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2021)
This article explores moderate and eclectic traditionalism beyond Kiai Haji Muhammad Hashim Ash’ari’s contribution in the shariah and Islamic jurisprudence of social politic (Fiqh al-Siyâsah al-Ijtimâ’iyah) in Indonesia. It is conceptual research referring to some of his works as well as discussion about his thought among Islamic scholars. Based on definition of moderation from the Qur’an, hadith, and some scholars’ opinion, Hashim can be best categorized as Islamic traditionalist figure who enforced both moderation and eclecticism. However, he maintained distinctive features compared to both traditionalist and modernist Islamic figures. It is mainly clear from both his thought and movement which rely on the Ahlus Sunnah wal Jama’ah in theology, four fiqh school leaders (Hanafiyah, Malikiyah, Syafi’iyah dan Hambaliyah), and thariqah sufiyah mu’tabarah. Additionally, he showed appreciation and promoted for adaptation to both local and foreign idea that later inspired distinctive religiosity in Indonesia. This particularly applies in the concept of relation between Islamic law and nationalism, jihad, political fiqh and governmental system in Islam. تستكشف هذه الورقة الوسطية التقليدية والانتقائية التي ساهمها كياهي حاجي محمد هاشم الأشعري في الشريعة الإسلامية وفقه السياسة الاجتماعية. إنه بحث مفاهيمي يشير إلى بعض أعماله وكذلك مناقشة حول أفكاره كعلماء المسلمين. بناءً على تعريف الوسطية من القرآن والحديث وبعض آراء العلماء، يمكن تصنيف هاشم بشكل أفضل على أنه الشخصية الإسلامية التقليدية التي فرضت الوسطية والانتقائية. ومع ذلك، فقد حافظ على سمات مميزة مقارنة بكل من الشخصيات الإسلامية التقليدية والحداثية. يتضح بشكل أساسي من فكره وحركته اللذين يعتمدان على أهل السنة والجماعة في العقيدة، قادة المذاهب الفقهية الأربعة (حنفية، المالكية، الشافعية والحبلية) والطريقة الصوفية المعتبرة. بالإضافة إلى ذلك، أظهر التقدير والترويج للتكيف مع الأفكار المحلية والأجنبية التي ألهمت لاحقًا التدين المميز في إندونيسيا. وهذا ينطبق بشكل خاص على مفهوم العلاقة بين الشريعة الإسلامية والوطنية والجهاد وفقه السياسية والنظام الحكومي في الإسلام.